Pengaruh Gaya Mengajar Guru dan Interaksi Teman Sebaya terhadap Keaktifan Belajar Siswa Kelas IX di SMP Negeri 5 Tulungagung - Arum Kusumawati; Nailariza Umami (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study was to determine the effect of teacher teaching style and peer interaction on the effectiveness of learning of grade IX students at SMP Negeri 5 Tulungagung. This study used quantitative descriptive research. The number of samples in this study was 112 grade IX students at SMP Negeri 5 Tulungagung. The research instrument used a questionnaire and observation. The data analysis techniques used in this study were classical assumptions (normality test, linearity test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing (t test and f test) and coefficient of determination with the help of SPSS 26 for windows program. The results of the study partially tcount> ttable which is 13.616> 1.659 and a significance value of 0.000 <0.05, thus it can be concluded that there is a significant influence between teacher teaching style (X1) on learning activity (Y) of grade IX students at SMP Negeri 5 Tulungagung. Furthermore, the peer interaction variable (X2) has a calculated t value > t table, namely 2.333 > 1.659 and a significance value of 0.021 < 0.05. Thus, it can be concluded that there is a significant influence between peer interaction (X2) on the learning activity (Y) of class IX students of SMP Negeri 5 Tulungagung.